2020
DOI: 10.1080/14479338.2020.1825089
|View full text |Cite
|
Sign up to set email alerts
|

Rare gems or mundane practice? Resource constraints as drivers of frugal innovation

Abstract: Frugal innovation and related concepts are receiving increasing scholarly attention. While recent progress in the conceptualisation of frugal innovation as a phenomenon has been considerable, insights into the antecedents of frugal innovation remain relatively poor. We add to this literature by systematically conceptualising, theorising and empirically testing the relationship between resource constraints and the propensity of firms to produce frugal innovations, drawing on concepts of problemistic search and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…They consume minimal necessary resources (Brem et al, 2017). Despite scant empirical evidence, the extant literature has confirmed risk-taking behavior, proactiveness (Dost and Khan, 2021), leadership (Iqbal et al, 2021a), university-industry relationship (Fischer et al, 2021) and firm-level resource constraints (Ploeg et al, 2021) as being strong antecedents of FI. However, Dwiedienawati et al (2021) recommended exploring further potential predictors of FI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They consume minimal necessary resources (Brem et al, 2017). Despite scant empirical evidence, the extant literature has confirmed risk-taking behavior, proactiveness (Dost and Khan, 2021), leadership (Iqbal et al, 2021a), university-industry relationship (Fischer et al, 2021) and firm-level resource constraints (Ploeg et al, 2021) as being strong antecedents of FI. However, Dwiedienawati et al (2021) recommended exploring further potential predictors of FI.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021a), university–industry relationship (Fischer et al. , 2021) and firm-level resource constraints (Ploeg et al. , 2021) as being strong antecedents of FI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have empirically confirmed various elements that significantly spur frugal innovation, i.e., internal capabilities, surrounding innovation ecosystems, and overarching institutional frameworks ( Fischer et al, 2021 ). Others include firm-level resource constraints ( Ploeg et al, 2021 ), internal and external sources of knowledge ( Dost et al, 2019 ), and bricolage capability ( dos Santos et al, 2020 ). Furthermore, transformational and sustainable leadership ( Iqbal et al, 2020b ; Lei et al, 2021 ) exhibited significant frugal innovation predictors.…”
Section: Introductionmentioning
confidence: 99%
“…FI was initially proposed based on cost constraints to serve lowincome customers in DCs (Hossain, 2013) because innovation in developing economies is challenging due to the resources lack, infrastructure lack and limited access to this infrastructure and economic and financial constraints (Ahuja & Chan, 2014;Sun et al, 2016). However, in companies with experienced management, limited resources at the company level strongly influence the companies' willingness to participate in FI (Ploeg et al, 2020). In these conditions, it is necessary to improvise solutions using existing resources in a particular way to meet the challenges and opportunities in restricted environments (Santos et al, 2020).…”
Section: Frugal Resourcementioning
confidence: 99%